Myocarditis and/or pericarditis risk after mRNA COVID-19 vaccination: A Canadian head to head comparison of BNT162b2 and mRNA-1273 vaccines. Issue 32 (30th July 2022) - Abraham, Natalia; Spruin, Sarah; Rossi, Tanya; Fireman, Bruce; Zafack, Joseline; Blaser, Christine; Shaw, Amanda; Hutchings, Kimberley; Ogunnaike-Cooke, Susanna
Highlights: Myocarditis/pericarditis is a rare adverse event observed following COVID-19 mRNA vaccination. Myocarditis/pericarditis risk is higher after mRNA-1273 than after BNT162b2. The product-specific difference is highest in young males within 7 days after the second dose. Abstract: Background: Canadian and international data suggest the risk of myocarditis and/or pericarditis is elevated during the week after mRNA COVID-19 vaccination, particularly in younger age groups, in males, and after second doses. Objectives: This article examines whether there is a product-specific difference in the risk for myocarditis and/or pericarditis between the two mRNA vaccines administered in Canada: BNT162b2 (Pfizer-BioNTech Comirnaty) and mRNA-1273 (Moderna Spikevax). Materials and methods: Reporting rates of myocarditis and/or pericarditis were calculated from reports received by the Canadian Adverse Events Following Immunization Surveillance System from December 2020-March 2022. Excess cases and attributable incidence among individuals aged 18–39 were estimated for each vaccine in comparison with background rates from 2015 to 2019. Head-to-head comparisons used Poisson regression, conditioned on week of vaccine administration, to estimate rate ratios for the week after mRNA-1273 vaccination versus the week after BNT162b2, by age and sex as well as overall. Analyses were restricted to May 30–March 13, 2021, when heightened media awareness was unlikely to have affected reporting rates for the two products differentially. Results: In 18–29 year-old males who received a second dose of mRNA COVID-19 vaccine, attributable risk of myocarditis and/or pericarditis was found to be 5.69 (95% CI: 4.07 – 7.95; p < 0.001) times higher among mRNA-1273 recipients (n = 106) as compared to BNT162b2 recipients (n = 33). In the same group, Poisson regression modelling estimated that the risk of myocarditis and/or pericarditis was 4.72 (p-value = <0.001) times higher after mRNA-1723 compared to BNT162b2 vaccination. Conclusions: The risk of myocarditis and/or pericarditis is higher after mRNA-1723 vaccination than BNT162b2 vaccination in those aged 18–39 years, especially in males aged 18–29 years, where the risk is several times higher.